Impact of exogenous alpha tocopherol on peanut seedlings (Arachis hypogaea L.) treated by norflurazon - Manaa, Imene; Djebbar, Reda; Abrous-Belbachir, Ouzna (Acta Biologica Szegediensis, 2020)
Norflurazon 100 µM alone or in combination with α-tocopherol (0.25 mM) was applied in pre-emergence of peanut seedlings (Arachis hypogaea L.). Norflurazon treatment allowed to partially or totally photobleach plants which were noticeably smaller than the control. Norflurazon impaired the photosynthetic activity by decreasing photosynthetic pigments (carotenoids and chlorophylls) and by reducing quantities of soluble sugar. The determination of malondialdehyde (MDA) showed that its content was higher in treated plants in relation with enhancement of reactive oxygen species by the herbicide and decreased the endogenous α-tocopherol. The addition of exogenous α-tocopherol reduced the damage done by the herbicide at the membrane level because of the MDA content was less important than in norflurazon treated seedlings. Furthermore, the norflurazon decreased the glutathione S-transferase (GST) activity in the leaves and the roots of peanut seedlings, while it increased the level of reduced glutathione. This activity decreased even more with the application of exogenous α-tocopherol in combination with the herbicide. The herbicide alone or in association with the antioxidant α-tocopherol increased ascorbic acid content. The supplementation of α-tocopherol did not decrease the phytotoxicity of norflurazon although we observed a decrease in MDA content.